DAF in diabetic patients is subject to glycation/inactivation at its active site residues. (January 2018) - Flückiger, Rudolf; Cocuzzi, Enzo; Nagaraj, Ram H.; Shoham, Menachem; Kern, Timothy S.; Medof, M. Edward
Highlights: DAF protein is subject to nonenzymatic glycation in vivo . The nonenzymatic glycation alters residues clustered at the junction of CCPs 2 and 3 which comprise DAF's active site. The alterations can impair DAF's function. This could lead to abnormal activation of system complement on self-cells and increased T cell activation. Abstract: Decay accelerating factor (DAF or CD55) is a cell associated C3 and C5 convertase regulator originally described in terms of protection of self-cells from systemic complement but now known to modulate adaptive T cell responses. It is expressed on all cell types. We investigated whether nonenzymatic glycation could impair its function and potentially be relevant to complications of diabetes mellitus and other conditions that result in nonenzymatic glycation including cancer, Alzheimer's disease, and aging. Immunoblots of affinity-purified DAF from erythrocytes of patients with diabetes showed pentosidine, glyoxal-AGEs, carboxymethyllysine, and argpyrimidine. HPLC/MS analyses of glucose modified DAF localized the sites of AGE modifications to K 125 adjacent to K 126, K 127 at the junction of CCPs2-3 and spatially near R 96, and R 100, all identified as being critical for DAF's function. Functional analyses of glucose or ribose treated DAF protein showed profound loss of its regulatory activity. The data argue that de-regulated activation of systemic complement and de-regulated activation of T cells and leukocytes could result from non-enzymatic glycation of DAF.